2001
DOI: 10.1021/bi010187m
|View full text |Cite
|
Sign up to set email alerts
|

Tryptic Digestion of Soybean Lipoxygenase-1 Generates a 60 kDa Fragment with Improved Activity and Membrane Binding Ability

Abstract: Lipoxygenases are key enzymes in the metabolism of unsaturated fatty acids. Soybean lipoxygenase-1 (LOX-1), a paradigm for lipoxygenases isolated from different sources, is composed of two domains: a ∼30 kDa N-terminal domain and a ∼60 kDa C-terminal domain. We used limited proteolysis and gel-filtration chromatography to generate and isolate a ∼60 kDa fragment of LOX-1 ("mini-LOX"), produced by trypsin cleavage between lysine 277 and serine 278. Mini-LOX was subjected to N-terminal sequencing and to electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 47 publications
(84 reference statements)
8
81
1
1
Order By: Relevance
“…26 Under the same experimental conditions, we found here that ETYA did not affect the membranebinding ability of LOX-1 nor its dependence on calcium ions (Table 2), whereas the addition of glycerol (5%) increased the binding of LOX-1 to membranes significantly (up to 175% of the controls), without affecting the calcium-dependence of this process (Table 2).…”
Section: Effect Of Etya or Glycerol On Lox-1 Activity And Membrane-bisupporting
confidence: 55%
See 2 more Smart Citations
“…26 Under the same experimental conditions, we found here that ETYA did not affect the membranebinding ability of LOX-1 nor its dependence on calcium ions (Table 2), whereas the addition of glycerol (5%) increased the binding of LOX-1 to membranes significantly (up to 175% of the controls), without affecting the calcium-dependence of this process (Table 2).…”
Section: Effect Of Etya or Glycerol On Lox-1 Activity And Membrane-bisupporting
confidence: 55%
“…The structural effects of ETYA and glycerol were correlated with their effects on catalytic efficiency and membrane-binding ability of LOX-1, two critical aspects of the biological activity of the enzyme. 1,26 All our data point towards the remarkable structural stability of soybean LOX-1, whose crystal structure is essentially preserved in solution under various conditions.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Membrane Binding Assays-Negatively charged, unsaturated phosphatidylcholine liposomes were prepared in phosphate-buffered saline using the liposome kit (Sigma) as reported (17). The size of the vesicles was ϳ2 m, as determined under the microscope by comparison with the size (10 Ϯ 0.5 m) of Mono Q beads (Amersham Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…The size of the vesicles was ϳ2 m, as determined under the microscope by comparison with the size (10 Ϯ 0.5 m) of Mono Q beads (Amersham Biosciences). The binding of FAAH to liposomes was determined essentially as reported (17). Preliminary experiments showed that incubation of liposome suspensions corresponding to 1 mol of phosphatidylcholine (50 l) with 100 pmol of FAAH (corresponding to 2 M) for 0 -60 min at 25°C yielded the highest amount of bound FAAH (i.e.…”
Section: Methodsmentioning
confidence: 99%